White Magic, Black Humour: Ella D’Arcy’s Narrative Strategies - Heather Marcovitch (Cahiers Victoriens et Edouardiens)
Of the New Woman writers who wrote humour, Ella D’Arcy is one of the more elusive. Her humorous writing takes the form of satire which depends on a double reading. A straightforward reading of her stories sympathizes with her male protagonists engaging in unsuitable romances and bad marriages. A resisting reading, however, shows these men as egotistical fools whose efforts to set the terms of their romances backfire. D’Arcy’s double reading is dependent on her audience and therefore was rarely appreciated by her mostly male reviewers. Through her letters to her publisher John Lane, we also see how this doubleness informed her relationships with him and Henry Harland, the editor of The Yellow Book and D’Arcy’s employer and friend. Humour was not just a mode in D’Arcy’s writing, but a strategy in her job and particularly in her relationships with editor Henry Harland and publisher John Lane. Her letters to Lane, housed at the Clark Library at the University of California, Los Angeles, reveal an Austenian humour that was D’Arcy’s protection against these men’s capricious behaviours. We see D’Arcy adopting this ironic pose as she tries to keep The Yellow Book on schedule in the aftermath of Oscar Wilde’s arrest, and as she copes with Harland’s regular tantrums and Lane’s indifference. This paper explores the double readings of her stories and their connection to D’Arcy’s work at The Yellow Book.